1992
DOI: 10.1007/bf00993271
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of mast cells with the nervous system ?Recent advances

Abstract: This article reviews recent advances in the understanding of mast cell-nervous system interactions. It is drawn largely from work published within the last ten years, and discusses the anatomical and biochemical evidence of a functional connection between mast cells and the nervous system, and the implications that such a relationship may have for normal and abnormal physiological functioning. Mast cells are found at varying levels of association with the nervous system; in CNS parenchyma (mainly thalamus), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 143 publications
2
83
0
Order By: Relevance
“…The evidence for mast cells in the brains of birds and rodents is vast, although the precise function of these immune cells in the brain remains unknown (e.g., Silver et al, 1992Silver et al, , 1993Silverman et al, 1994Silverman et al, , 1995Wilhelm et al, 2000;Zhuang et al, 1993;Dimitriadou et al, 1990;Johnson et al, 1991;Johnson and Krenger 1992). In the present study, two independent markers revealed the presence of mast cells in the brains of female prairie voles.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…The evidence for mast cells in the brains of birds and rodents is vast, although the precise function of these immune cells in the brain remains unknown (e.g., Silver et al, 1992Silver et al, , 1993Silverman et al, 1994Silverman et al, , 1995Wilhelm et al, 2000;Zhuang et al, 1993;Dimitriadou et al, 1990;Johnson et al, 1991;Johnson and Krenger 1992). In the present study, two independent markers revealed the presence of mast cells in the brains of female prairie voles.…”
Section: Discussionsupporting
confidence: 44%
“…Mast cells are granulocytic immune cells found peripherally in mucosal and serosal tissues, as well as in the CNS, often in close apposition to neurons and blood vessels (Dimitriadou et al, 1990;Johnson et al, Seeldrayers, 1991;Johnson and Krenger, 1992). Mast cells play an important role in innate (nonspecific) immune responses and are capable of secreting numerous substances, including neuro-transmitters, biogenic amines, and proteoglycans (Galli, 1990;Lambracht-Hall et al, 1990), and they degranulate in response to immunoglobulin E (IgE) and antigen stimulation (reviewed in Johnson and Krenger, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MC are granulocytic immune cells that are mainly observed in perivascular locations in mucosal and serosal tissues (103,104). They are also resident within the normal nervous system, and are often observed in close apposition to neurons in various peripheral tissues (103,105). MC are associated classically with the hypersensitivity reactions involving the interaction of allergens and cell-fixed IgE (104,106).…”
Section: Ngf and The Immune Systemmentioning
confidence: 99%
“…Considerable evidence published by many investigators indicates that MC and their endogenous products are strongly implicated not only in the classical immune processes, but also in neurophysiologic and neuropathologic events. MC are implicated in inflammatory and/or autoimmune diseases, such as multiple sclerosis, through the release of biologically active compounds, including NGF (105,106,108).…”
Section: Ngf and The Immune Systemmentioning
confidence: 99%